If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + 4c = 6c + -1(19 + 13) Combine like terms: 19 + 13 = 32 -12 + 4c = 6c + -1(32) Multiply -1 * 32 -12 + 4c = 6c + -32 Reorder the terms: -12 + 4c = -32 + 6c Solving -12 + 4c = -32 + 6c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6c' to each side of the equation. -12 + 4c + -6c = -32 + 6c + -6c Combine like terms: 4c + -6c = -2c -12 + -2c = -32 + 6c + -6c Combine like terms: 6c + -6c = 0 -12 + -2c = -32 + 0 -12 + -2c = -32 Add '12' to each side of the equation. -12 + 12 + -2c = -32 + 12 Combine like terms: -12 + 12 = 0 0 + -2c = -32 + 12 -2c = -32 + 12 Combine like terms: -32 + 12 = -20 -2c = -20 Divide each side by '-2'. c = 10 Simplifying c = 10
| 12x^2-11x=0 | | -10x+1-7x=17x+7 | | (8x+3)(8x-3)=0 | | -7(5x+3)=-91 | | -10+1-7x=17x+7 | | 3+4(p+2)=2p+3(p+4) | | -99-6x=171+12x | | -59-6x=95+x | | -5x-160=4x+47 | | 2(x-5)-8=20 | | 3x^4-24x^3+49x^2-8X+16=0 | | 3x-3y=8 | | -42-2x=-6x+34 | | 64x^2=9 | | y=x^2+4x-9 | | 4(x-2)+4=5x+4 | | -109-2x=43-10x | | -8x-152=x+100 | | 48-8x=16 | | (x-8)(3x+1)=0 | | 0+0=1 | | -3x-92=7x+138 | | 9x+2=4x-7 | | 0.5k(11-k)+(6-(k+1))=0.5(k+1)(11-(k+1)) | | 5x-56=112+11x | | 7(3x+2)=224 | | 0.5k(11-k)+(6-k+1)=0.5(k+1)(11-(k+1)) | | -113-4x=55-12x | | 0.5k(11-k)+(6-(k+1))=0.5(k+1)(11-k+1) | | -104+10x=50+3x | | x=4-7 | | 0.5k(11-k)+(6-k+1)=0.5(k+1)(11-k+1) |